Adjustment of the Foundation's Articles of Association Judging from the Law Enforcement Perspective - Fitri Pratiwi Rasyid; Audyna Mayasari Muin (Musamus Law Review, 2019)
According to Indonesia Foundation Law, No. 16/ 2001, as amended by Law No. 28/2001, article 1(1) stipulates that Foundation is a legal entity that has separated assets to achieve specific objectives in the social, religious, and humanitarian fields, which has no members. Importantly, this regulation has required a Foundation to have legal entities status. In fact, some Foundations in Indonesia have existed, and continuously functioning performs business activity without having legal entities status. This phenomenon should be banned as clearly regulated in the Law that foundations shall not be drawn on as platforms of business unless through other business entities.